Manajemen Komunikasi Kepala Madrasah Dalam Meningkatkan Profesionalisme Guru - Apri Ningsih Zebua (Getpress Management Journals, 2025)
This study aims to analyze the role of the principal's communication management in improving teacher professionalism at Madrasah Tsanawiyah Madinatul 'Ulum, Medan Labuhan District. The method used is a case study with primary data collection through in-depth interviews with principals and teachers, as well as secondary data from literature in the form of scientific journal articles, theses, theses, and dissertations. Data analysis was carried out with an analytical descriptive approach through the stages of data reduction, data presentation, and conclusion drawing. The results showed that effective and transparent principal communication, the use of easy-to-understand language, and openness to teacher input significantly contributed to building a harmonious work climate and supporting teacher professionalism. In addition, clear assignments and appreciation of teacher performance also increase the motivation and productivity of educators. However, there are also challenges in the form of miscommunication and inconsistent meeting schedules, which become evaluation materials for future improvements. Thus, good communication management from the principal is a key factor in encouraging the improvement of the quality and professionalism of teachers in madrasah.